PENGARUH PERDAGANGAN BEBAS AFTA DAN ACFTA BAGI INDUSTRI DALAM NEGERI - Agustina Balik (SASI, 2015)
ASEAN Free Trade Area (AFTA) is a form of trade cooperation ASEAN region in the form ofan agreement to create a situation that is balanced and fair trade through tariff reduction ingoods trade where there is no tariff barriers (import duty 0-5%) and non-tariff barriers forcountry- ASEAN member countries. ACFTA is a free-trade area between ASEAN members andChina. Indonesia as one of the ASEAN member countries still have some obstacles that showsour unpreparedness to face AFTA, which are: in terms of law enforcement, agencies shouldparticipate facilitate trade and business world often appears to be even indicted for corruption. AFTA brings a number of advantages, namely goods originally manufactured with high costs will be obtained consumers with cheaper prices and a region fully integrated together, the ASEAN region will be more attractive as investment land. What to do Indonesia in order to properly facing AFTA and ACFTA and to compete with other countries are: Promotion and market penetration, increase in efficiency of domestic production, Improved quality of human resources, protection of small industries, and efforts to improve the competitiveness of the agricultural sector